Transparent character, or Syndrome of Briseis - Mojeiko, Marina A.; Sevastov, Kirill V. (Journal of the Belarusian State University. Sociology, 2026)
A phenomenon of artistic culture that can be named a transparent character is modelled. This is a personage who is fundamentally important for the development of the plot and the development of the narrative, but who is practically deprived of the status of an active subject (the reader is not informed about his thoughts, his feelings, his assessment of what is happening). He does not act as an actor in any action, but his removal from the text would lead to the complete destruction of the plot. The phenomenon of a transparent character is considered using classical culture (ancient literature and medieval chronicles) and post-non-classical culture (postmodernist novel). Particular attention is paid to identifying an alternative tendency, which consists in the fact that a retrospective reaction to a cultural text consciously and purposefully endows a transparent character with detailed and emotionally charged subjective characteristics and a worldview position.